Incidence of intestinal form of haemorrhagic septicaemia in cattle and buffaloes in Orissa - Nayak, B C; Patro, D N; Pradhan, R K; Pradhan, S K; Das, B R; Mohanty, T N; Mohanty, D N; Tripathy, S B (The Indian Journal of Animal Sciences, 2012)
Three outbreaks of intestinal form of haemorrhagic septicaemia in cattle and buffaloes affecting 1.3% (54/3928) of total population with a case fatality of 46.29 (25154) and a morbidity rate of 0.3 to 9.09 % were recorded. The most significant clinico-pathological features were bloody diarrhoea, ulceration in the mouth cavity and on the abomasal mucosa, marked haemorrhagic gastroenteritis associated with moderate affection of respiratory tract and sub-cutaneous tissues of the throat, brisket and face. The laboratory examination confirmed the isolation of Pasteurella multocida organisms and the disease was combated by treatment and prophylactic vaccination of the population at risk.